2017
DOI: 10.1002/jcsm.12219
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial investigating the efficacy of targeted nutrition as adjunct to exercise training in COPD

Abstract: BackgroundEvidence regarding the efficacy of nutritional supplementation to enhance exercise training responses in COPD patients with low muscle mass is limited.The objective was to study if nutritional supplementation targeting muscle derangements enhances outcome of exercise training in COPD patients with low muscle mass.MethodsEighty‐one COPD patients with low muscle mass, admitted to out‐patient pulmonary rehabilitation, randomly received oral nutritional supplementation, enriched with leucine, vitamin D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 31 publications
0
112
0
1
Order By: Relevance
“…Although an increase in LBM would have been preferable, this might have been achieved had an exercise programme been specified, as was recently demonstrated in an RCT of a nutritional intervention combined with high-intensity exercise in patients with COPD and low muscle mass. 37 Moreover, any weight gain in this patient group could be beneficial in terms of survival. 36 The impact of TMN on lipid profiles was generally favourable, as expected based on studies of high-dose omega-3 PUFAs in healthy adults.…”
Section: Discussionmentioning
confidence: 91%
“…Although an increase in LBM would have been preferable, this might have been achieved had an exercise programme been specified, as was recently demonstrated in an RCT of a nutritional intervention combined with high-intensity exercise in patients with COPD and low muscle mass. 37 Moreover, any weight gain in this patient group could be beneficial in terms of survival. 36 The impact of TMN on lipid profiles was generally favourable, as expected based on studies of high-dose omega-3 PUFAs in healthy adults.…”
Section: Discussionmentioning
confidence: 91%
“…Calder and colleagues47 investigated 3 months of multimodal nutritional intervention including high-quality protein, vitamin D and n−3 fatty acids versus an isocaloric control, and showed positive effects on blood pressure, blood lipids and on exercise-induced fatigue. A Dutch trial48 investigated the efficacy of a similar multimodal nutritional intervention as adjunct to 4 months of high-intensity exercise training. Muscle mass and physical performance improved in both groups, but the intervention group showed additional effects on nutritional status and PA compared with placebo.…”
Section: Nutritional Modulation With(out) Exercise Trainingmentioning
confidence: 99%
“…Alvin L. Barach (67) and Thomas Petty (68) were the first to suggest that exercise was a key component of pulmonary rehabilitation. It has been shown that exercise together with protein supplementation is the most efficacious management for COPD (69)(70)(71)(72). An exercise intervention prescribed in 58 frail older patients after hospital admission for acute COPD exacerbation in improved muscle strength, balance, and exacerbation (73,74).…”
Section: Figure 2 Mechanisms Of Sarcopenia In Persons With Copdmentioning
confidence: 99%